Eudemonia of People Living with HIV at an Anti-Retroviral Therapy Center, Ron, Gadag District - A Mixed Method Feasibility Study - Stephen John; Dileep S Natekar (RGUHS Journal of Nursing Sciences)
Background In the realm of health and wellbeing the cursed part is the illness. Times elapsed health problems and challenges evolved constantly. In 1980s the first case of HIV Human Immunodeficiency Virus was reported and according to World Health Organization WHO 36.9 million people worldwide are living with HIVAIDS Acquired Immunodeficiency Syndrome.Aim This study aimed to explore the meaning of lived experiences of people living with HIV PLHIV and evaluate the effectiveness of health interventions on the state of health of PLHIV at an Anti-retroviral therapy ART center Ron Gadag District.Methods A sequential exploratory mixed-method study was conducted from August 2022 to September 2022. The qualitative strand with five samples explored lived experiences of PLHIV to develop health related counselling programme and quantitative strand with 14 samples tested the health-related counselling programme developed based on the data extracted from qualitative strand leading to first level integration in addition to administration of oral zinc 20 mgday for one month. Qualitative data analysis was done using QDA Miner lite version 3.0 and quantitative data analysis was done using IBM SPSS version 29.0 followed by mixing of data by integrated analysis.Results After qualitative analysis six themes and twenty-one sub-themes were derived in development of phenomenology. After quantitative analysis H1 amp H2 were accepted as P value obtained was 0.001 for df - 01 at 5 level of significance. The integrated analysis showed that findings from both the strands complemented supported and synergized the state of eudemonia among PLHIV.Conclusion The study concluded that administration of oral zinc supplementation and regular health related counselling sessions are effective strategies in maintaining eudemonia of people living with HIV amp AIDS.